1986
DOI: 10.1109/tassp.1986.1164983
|View full text |Cite
|
Sign up to set email alerts
|

The computation of line spectral frequencies using Chebyshev polynomials

Abstract: Abstract-Line spectral frequencies provide an alternate parameterization of the analysis and synthesis filters used in linear predictive coding (LPC) of speech. In this paper, a new method of converting between the direct form predictor coefficients and line spectral frequencies is presented. ,The system polynomial for the analysis filter is converted to two even-order symmetric polynomials with interlacing roots on the unit circle. The line spectral frequencies are given by the positions of the roots of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(85 citation statements)
references
References 9 publications
(13 reference statements)
0
78
0
7
Order By: Relevance
“…Moreover, LPC coefficients are hard to manipulate to perform timbre transformations. Later related approaches, like Line Spectral Frequencies (LSF) [15] or cepstrum-based techniques [14], partially improve some of these drawbacks. However, the parameters of these models are hard to manipulate in order to obtain natural timbre variations, since they are not directly related to physical aspects of the human vocal production.…”
Section: Proposed Parametric Model Of Spectral Envelopementioning
confidence: 99%
“…Moreover, LPC coefficients are hard to manipulate to perform timbre transformations. Later related approaches, like Line Spectral Frequencies (LSF) [15] or cepstrum-based techniques [14], partially improve some of these drawbacks. However, the parameters of these models are hard to manipulate in order to obtain natural timbre variations, since they are not directly related to physical aspects of the human vocal production.…”
Section: Proposed Parametric Model Of Spectral Envelopementioning
confidence: 99%
“…Instead, nonlinear functions of the reflection coefficients are often used as transmission parameters. These parameters are preferable because they have a relatively low spectral sensitivity [22]. It has been found that the line spectral frequency (LSF) representation of the predictor is particularly well suited for quantization and interpolation.…”
Section: Line Spectral Frequency (Lsf)mentioning
confidence: 99%
“…  is spectrally flattened, so that   should contain most of the spectral envelope of the given input speech frame. For a transmission purpose,  is expressed by the two reciprocal polynomials [4] :…”
Section: Equation 1 Is Equivalently Expressed In the Frequency Domain Asmentioning
confidence: 99%